2013
DOI: 10.1039/c3cc40461g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a cobalt(iv) ketimide with a squashed tetrahedral geometry

Abstract: Oxidation of [Li(THF)]2[Co(N=C(t)Bu2)4] with 1 equiv. of I2 generates Co(N=C(t)Bu2)4 in 85% yield. In the solid-state, this complex exhibits a squashed tetrahedral structure about the Co center. DFT calculations reveal this geometry arises, in part, to maximize ketimide-to-cobalt π-donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
73
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 23 publications
9
73
1
7
Order By: Relevance
“…17,18 In addition, the average Ta-N-C angle (172.7°) is indicative of sp hybridization at nitrogen, and is suggestive of significant π-donation from the ketimide to the metal, consistent with our ligand field analysis (see below). 3,4,6,19 Finally, the Ta-Cl bond lengths (2.498(1), 2.496(1) Å) are similar to those observed for other structurally characterized Ta(V) chlorides. 14,15,2022 …”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…17,18 In addition, the average Ta-N-C angle (172.7°) is indicative of sp hybridization at nitrogen, and is suggestive of significant π-donation from the ketimide to the metal, consistent with our ligand field analysis (see below). 3,4,6,19 Finally, the Ta-Cl bond lengths (2.498(1), 2.496(1) Å) are similar to those observed for other structurally characterized Ta(V) chlorides. 14,15,2022 …”
Section: Resultssupporting
confidence: 76%
“…These calculations demonstrated that the partially occupied orbitals ( d xz , d yz , d z 2 ) all possess considerable π* Co-N character. 6 Several Group 5 tetra(amido) complexes (e.g., M(NR 2 ) 4 ) have also been structurally characterized, and a comparison of their metrical parameters with those of 1, 2 , and 7 is similarly informative. Most interestingly, this class of materials does not exhibit the squashed tetrahedral geometry observed in M(N=C t Bu 2 ) 4 , and instead exhibit only slightly distorted tetrahedral geometries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations